Hasil Rakerda Program KKB Propinsi Sumatera Barat, thn. 1982/1983, 12 April-14 April 1982 (Badan Koordinasi Keluarga Berencana Nasional Propinsi Sumatera Barat, 1982)
On population and family planning programs in West Sumatera Province proceedings of a working conference.